2001
DOI: 10.2225/vol14-issue1-fulltext-3
|View full text |Cite
|
Sign up to set email alerts
|

Suppression subtractive hybridization PCR isolation of cDNAs from a Caribbean soft coral

Abstract: Transcriptomic studies of marine organisms are still in their infancy. A partial, subtracted expressed sequence tag (EST) library of the Caribbean octocoral Erythropodium caribaeorum and the sea fan Gorgonia ventalina has been analyzed in order to find novel genes or differences in gene expression related to potential secondary metabolite production or symbioses. This approach entails enrichment for potential non-"housekeeping" genes using the suppression subtractive hybridization (SSH) polymerase chain reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Transcriptomic approaches have found that Acropora cervicornis affected by white band disease has higher expression of genes associated with immune function than healthy colonies (Libro et al 2013), and expression of the gene for an antimicrobial peptide was up-regulated on exposure to the coral pathogen Vibrio coralliilyticus in Pocillopora damicornis (Vidal Dupiol et al 2011). Transcriptomic studies of soft corals are rare (Lopez et al 2011, Woo et al 2012), but one study of G. ventalina identified differential expression of many genes in response to microbial pathogenesis (Burge et al 2013b). Likewise, many coral genes have demonstrated differential expression in response to exposure to lipo poly saccharide and other pathogen-associated molecular patterns, which are often used as proxies for pathogen challenge (Kvennefors et al 2010, Weiss et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptomic approaches have found that Acropora cervicornis affected by white band disease has higher expression of genes associated with immune function than healthy colonies (Libro et al 2013), and expression of the gene for an antimicrobial peptide was up-regulated on exposure to the coral pathogen Vibrio coralliilyticus in Pocillopora damicornis (Vidal Dupiol et al 2011). Transcriptomic studies of soft corals are rare (Lopez et al 2011, Woo et al 2012), but one study of G. ventalina identified differential expression of many genes in response to microbial pathogenesis (Burge et al 2013b). Likewise, many coral genes have demonstrated differential expression in response to exposure to lipo poly saccharide and other pathogen-associated molecular patterns, which are often used as proxies for pathogen challenge (Kvennefors et al 2010, Weiss et al 2013).…”
Section: Introductionmentioning
confidence: 99%